Pengaruh Substitusi Tepung Daun Kelor (Moringa Oleifera) Terhadap Kadar Serat dan Tekstur Produk Snack Bar - Tata Indira; Dwi Sarbini (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The inadequate dietary fiber intake among the Indonesian population contributes to an increased risk of degenerative diseases, including diabetes mellitus. The utilization of Moringa oleifera L. as a functional food ingredient has attracted considerable attention due to its relatively high fiber content and its potential to enhance the nutritional quality of ready-to-eat food products. This study aimed to investigate changes in dietary fiber content and the textural characteristics of snack bars formulated with different levels of moringa leaf flour incorporation. An experimental approach employing a Completely Randomized Design (CRD) was applied, consisting of four treatment formulations with moringa leaf flour substitution levels of 0%, 5%, 10%, and 15%, each conducted in duplicate. Dietary fiber content was determined using the AOAC enzymatic-gravimetric method, while textural properties were evaluated using a Texture Analyzer. Statistical analysis was performed using One-Way ANOVA followed by Duncan’s Multiple Range Test (DMRT) to identify differences among treatments. The findings demonstrated that increasing the proportion of moringa leaf flour significantly affected both dietary fiber content and the texture of the snack bars (p < 0,05), with fiber levels increasing from 2,51% to 6,87%. The 15% formulation met the criteria for a high-fiber food product, whereas the 5% and 10% formulations were classified as sources of dietary fiber. These results highlight the potential of moringa leaf flour as a valuable ingredient for the development of highly functional snack bar products.